2007
DOI: 10.1007/s10661-007-9705-3
|View full text |Cite
|
Sign up to set email alerts
|

Relation of waste generation and composition to socio-economic factors: a case study

Abstract: To develop an effective waste management strategy for a given region, it is important to know the amount of waste generated and the composition of the waste stream. Past research has shown that the amount of waste generated is proportional to the population and the average mean living standards or the average income of the people. In addition, other factors may affect the amount and composition of waste. These are climate, living habits, level of education, religious and cultural beliefs, and social and public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
147
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(163 citation statements)
references
References 8 publications
(5 reference statements)
8
147
1
7
Order By: Relevance
“…Bandara, Hettiaratchi, Wirasinghe, and Pilapiiya (2007) in Sri Lanka revealed that number of employed people in HH contributed in increasing waste amount. In Turkey, Keser, Duzgun, and Aksoy (2012) measured unemployment rate as it signifies family's inability to generate higher income and found it to have significant negative impact on waste generation.…”
Section: Occupationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bandara, Hettiaratchi, Wirasinghe, and Pilapiiya (2007) in Sri Lanka revealed that number of employed people in HH contributed in increasing waste amount. In Turkey, Keser, Duzgun, and Aksoy (2012) measured unemployment rate as it signifies family's inability to generate higher income and found it to have significant negative impact on waste generation.…”
Section: Occupationmentioning
confidence: 99%
“…While it is apparent for more members of a HH to generate more waste, the phenomena of 'group living' and 'common consumption' can sometimes saturate the amount of waste being generated as number of generators increase (Gu et al, 2015;Ojeda-Benítez, Vega, & Marquez-Montenegro, 2008). Many studies have also supported HH size to have opposing effect on waste generation (Bandara et al, 2007;Irwan, Basri, & Watanabe, 2012;Kayode & Omole, 2011;Miezah et al, 2015;Ogwueleka, 2013;Qu et al, 2009). Large family are at an advantage when it comes to intensive utilization of materials such as food, paper and plastic, etc.…”
Section: Occupationmentioning
confidence: 99%
“…O aumento da geração de resíduos orgânicos, plásticos e papéis também foi mencionado em Kansal (2002), que afirma que a geração de resíduos sólidos nos países em desenvolvimento aumenta constantemente ao longo dos anos; esse aumento, segundo Bandara et al (2007), Papa- =58,04%), e Outros aumenta. A comparação desses resultados com os da correlação de Pearson revela que na medida em que a geração de resíduo orgânico aumenta, a geração de resíduo metal diminui; e na medida em que a geração do resíduo vidro diminui, aumenta a geração do resí-duo outros, enquanto, ao mesmo tempo, a geração de resíduo borracha diminui.…”
Section: Materiais E Métodosunclassified
“…Tal resultado aponta, com exceção da geração de resíduo orgânico, que diferentes regiões geram diferentes tipos de resíduos, pois utilizam diferentes tipos de materiais, podendo variar amplamente sua composição, o que corrobora o estudo de Emery et al (2004). Essa composição depende de diversas variáveis, como hábitos alimentares, tradições culturais, status socieconômico, nível de educação, crenças religiosas, atitudes sociais e públicas, e das condições climáticas (ENAYETULLAH; SINHA; KHAN, 2005;BANDARA et al, 2007).…”
Section: Materiais E Métodosunclassified
See 1 more Smart Citation